Ação do biocontrolador com atividade de indução de resistência no controle do crestamento bacteriano comum do feijoeiro (Phaseolus vulgaris L.) - Sbalcheiro, Cheila Cristina (2006)
The common bacterial blight of beans (CBCF), incited by the bacterium Xanthomonas axonopodis pv. phaseoli var. fuscans (Xapf), accounts for severe damages in the crop and reductions in grain yield and quality. The induction of resistance in plants against pathogens is an alternate method of disease control, which involves the activation of latent mechanisms of resistance in the plant. A number of bacteria able to stimulate one or more responses of defense and having biocontrol action have been isolated and characterized. Actinomicetos spp. is a bacterium capable of eliciting response of defense in some plants. The objective of this work was determine the potential of biocontroller of CBCF and its effect on enzymes linked to resistance induction. Two methods of application of the biocontroller have been evaluated: seed dressing and aspersion of above-groud plant parts. The disease was significantly controlled in the treatments where the seeds had been microbiolized with biocontroller. The enzymatic activity of the enzymes peroxidase, ß-1,3-glucanase, phenylalanine ammonia-liase and polyphenoloxidase showed differences among treatments and the different cycle dates of the crop. For the isoperoxidase system, intra and interpopulation differences, as well as quantitative difference, were observed between the treatments. The results demonstrate alteration in the activity of enzymes related to plant defense, promoted by the biocontroller of the bacterial blight of common beans